Exceptional sequences of line bundles on projective bundles - Altmann, Klaus; Hochenegger, Andreas; Witt, Frederik (MATHEMATICA SCANDINAVICA, 2025)
For a vector bundle E→ P^ we investigate exceptional sequences of line bundles on the total space of the projectivisation X=P(E). In particular, we consider the case of the cotangent bundle of P^. If =2, we completely classify the (strong) exceptional sequences and show that any maximal exceptional sequence is full. For general , we prove that the Rouquier dimension of D(X) equals X, thereby confirming a conjecture of Orlov.